LINGKUNGAN PENDIDIKAN PERSPEKTIF AL-QUR’AN - Ahmad Zain Sarnoto; Noor Farida (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2021)
This research is to examine the educational environment in the perspective of the Qur'an by using qualitative research methods. In discussing the interpretation of the Qur'an, the maudhu'i (thematic) method was chosen in this study to be able to find a comprehensive concept of the educational environment of the Qur'anic perspective, and to use qualitative methods to produce descriptive data whose results are presented in the form of qualitative. In addition, this research is based on library research, because the data are in the form of verses of the Qur'an and authoritative commentary books, and various written materials published in the form of books, journals, articles, websites, software. , magazines, and proceedings related directly or indirectly to research. Therefore, this dissertation is included in the type of qualitative research. The conclusion of this study is that the holistic education paradigm can be created through the integration of the educational environment with the elements of holistic totality in the Qur'an. This is based on the Qur'anic cues about the six elements of a holistic totality including: 1. Jismiah elements (physical and biological); 2. The element of nafsiah (psychic); 3. Spiritual elements (spiritual-transcendental); 4. Social elements; 5. Cultural elements; and 6. Environmental elements. So that it can form human beings who have character and are beneficial to fellow humans and the environment